Bacteriological Profile and Antimicrobial Susceptibility of Surgical Site Infections at a Tertiary Care Paediatric Hospital in North-West India - Savita Choudhary, Saroj Hooja, Nita Pal, Rajni Sharma, Bharti Malhotra (RUHS Journal of Health Sciences, 2025)
Introduction: Surgical site infections (SSI) are one of the most common healthcare-associated infections (HAI), morbid and costly to treat. Due to paucity of data in this region, this study was undertaken to assess the bacterial pathogens causing surgical site infection and selection of effective antibiotics against pathogens among paediatric patients undergoing surgery and risk factors associated with SSI. Methodology: This was a prospective hospital based descriptive type of observational study carried out at a tertiary care hospital in North-West India. The study was carried on a total of 108 samples from paediatric patients (0-14 years of age group) and their bacteriological profile and antibiogram were studied. Results: Out of 108 samples, a total of 110 bacterial isolates were obtained from 104 culture positive samples. E coli (58.2%) was the commonest bacterial isolate followed by Klebsiella spp. (20:0%), Staphylococcus aureus (10.9%), Enterobatcter aero-genes (7.3%), and Pseudomonas spp. (3.6%). In Gram-negative bacilli (E coli, Klebsiella spp., E aerogenes) none of the strains were susceptible to Ampicillin while all of them were susceptible to Polymyxin-B and Tigecycline (100%). Among the isolated Pseudomonas spp., 100% were susceptible to Aztreonam and Colistin. None of them were susceptible to Piperacillin plus Tazobactam, and Cefepime. S aureus was 100% susceptible to Vancomycin, Teicoplanin, Erythromycin, Linezolid, and Clindamycin while none of the isolates were susceptible to Ampicillin, Piperacillin plus Tazobactam, Cefoxitin, and Cefepime. Conclusion: Gram-negative organisms with multiple drug resistance including extended spectrum β-lactamase (ESBL) producing Enterobacteriaceae were commonly associated with postoperative surgical site infection. Infection prevention and control (IPC) with both surveillance and control components could lower SSI rates significantly.